The opportunities for and barriers to antimicrobial resistance surveillance by lot quality assurance sampling in livestock: Findings from interviews with stakeholders in Germany - Christopher Pell; René Wagner; Christa Ewers; Constance Schultsz; Timo Homeier-Bachmann; Carsten Heydel; Frank van Leth; Christian Menge (One Health)
Introduction: Bacterial pathogens exhibiting antimicrobial resistance (AMR) are a health threat for humans, companion animals and livestock. Surveillance underpins appropriate AMR responses, but can be biased or expensive. Surveillance using Lot Quality Assurance Sampling (LQAS) has shown promise in human health settings; more evidence on its applicability and acceptability in livestock populations is needed. Drawing on in-depth interviews, this article examines stakeholder perspectives on LQAS for AMR surveillance in livestock in Germany. Methods: Twenty-five stakeholders were interviewed. They included employees of German universities, research institutes, Federal animal health services / veterinary laboratories, animal producer associations, and veterinarians. Detailed notes of online interviews were analyzed using a framework approach. Results: Respondents were concerned about AMR in livestock and also about restrictions on antibiotic treatment options. They described the multifaceted, legally prescribed data gathering for farmers to monitor antibiotic consumption and the widespread use of antibiograms to guide treatment in Germany. Respondents saw potential benefits of LQAS for AMR surveillance, in terms of reducing the sample sizes and the need for antibiotic susceptibility tests, but there were questions about surveilling commensal bacteria, with concerns about it leading to further restrictions on antibiotic consumption and driving food production overseas. Conclusion: An LQAS approach to AMR surveillance requires locally responsive guidance to alleviate concerns about further restriction of treatment options (and about animal welfare). Given existing data collection, recording and reporting burden for farmers and veterinarians, early engagement is needed to agree the rationale and benefits of LQAS, particularly if surveilling resistance in commensal bacteria is considered.